2016
DOI: 10.1049/mnl.2016.0496
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of partial discharge characteristics of cross‐linked polyethylene nanocomposites over microcomposites for electrical insulation application

Abstract: Partial discharge (PD) study is considered as an effective tool to evaluate the condition of electrical insulation. The PD test results for crosslinked polyethylene (XLPE)/silica microcomposite (30, 40, 50 wt%) and nanocomposite (1, 2, 3, 4, 5, 10 wt%) samples in comparison to virgin (0 wt%) samples is presented. It has been found that nanocomposite samples have lower PD formation, higher discharge inception voltage (DIV) as well as breakdown voltage as compared with virgin and microcomposite samples. From the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Decrease in surface energy with the addition of nanofiller is reported in 27 . As it is already shown in our previous research reported in 17 , the optimal content of nanofiller is XLPE/silica nano 5 wt %. Also, for Octylsilane-modified optimal content of XLPE/silica nano 3 wt %, there is considerable change in contact angle from 94.59 o to 100.29 o .…”
Section: Secondary Crystallization and Multiple Melting Pointssupporting
confidence: 69%
See 4 more Smart Citations
“…Decrease in surface energy with the addition of nanofiller is reported in 27 . As it is already shown in our previous research reported in 17 , the optimal content of nanofiller is XLPE/silica nano 5 wt %. Also, for Octylsilane-modified optimal content of XLPE/silica nano 3 wt %, there is considerable change in contact angle from 94.59 o to 100.29 o .…”
Section: Secondary Crystallization and Multiple Melting Pointssupporting
confidence: 69%
“…For unmodified case, XLPE/silica nano 5 wt % sample has the lowest PD activity with highest DIV and BDV. 17 This content is considered as the optimal content for PD characteristics. In case of Octylsilane surface modified XLPE/silica nanocomposites, the nano 3 wt % sample is having the lowest PD present as shown in Figure 6 with highest BDV and DIV as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations